2020
DOI: 10.21608/eajbsf.2020.114538
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Some Insecticides Against Cotton Leafworm, Spodoptera littoralis (Boisd) (Lepidoptera: Noctuidae).

Abstract: The toxicological effects of some insecticide mixtures (chlorpyrifos, pyridalyl, chlorantraniliprole, emamectin benzoate, and methoxyfenozide), against the 3 rd instar of Spodoptera larvae were evaluated. The results indicated that, LC 50 values for each insecticide were 12.44, 0.88, 0.08, 0.16 and 3.35 mg L-1 respectively, and 0.458, 0.009, 0.0014 and 0.357 mg L-1 respectively.Also, the LC 50 values of chlorpyrifos are increased by larvae weight increased. LC 50 values of chlorpyrifos as a function of postfee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Abd El-Naby, (2019) studied the effect of two photosensitizers at concentrations10 -3 and 10 -2 M caused a highly significant reduction in S. littoralis population in the tomato field during seasons 2015 and 2016 and magnesium chlorophyllin more effective than copper chlorophyllin. In addition, the reduction in S. littoralis in the cotton field ranged between 74.2 and 90.2% at the first season and between 64.9% and 94.8% in the second season post-treatment (Ahmed et al, 2018). Biochemical studies using the semi-field technique.…”
Section: Field Experimentalmentioning
confidence: 99%
“…Abd El-Naby, (2019) studied the effect of two photosensitizers at concentrations10 -3 and 10 -2 M caused a highly significant reduction in S. littoralis population in the tomato field during seasons 2015 and 2016 and magnesium chlorophyllin more effective than copper chlorophyllin. In addition, the reduction in S. littoralis in the cotton field ranged between 74.2 and 90.2% at the first season and between 64.9% and 94.8% in the second season post-treatment (Ahmed et al, 2018). Biochemical studies using the semi-field technique.…”
Section: Field Experimentalmentioning
confidence: 99%
“…The insect growth regulator is interfered with insect growth and development by inhibiting chitin synthesis in insects, lowest toxic effect to mammals, birds, and fish (Flint and Smith, 1977) and (Mokbel et al 2017) cited that, emamectin benzoate is a new and effective insecticide used against lepidopteran insect pests. Also, the mixing of these compounds with traditional insecticides increases the efficiency of these insecticides (Abdel-Sattar and EL-Guindy 1988); (Ahmed 2020) and (Abdel Aziz 2019). Abdel-Mageed et al (2006) reported that spinosad gave moderately initial and residual effects when tested alone.…”
mentioning
confidence: 99%